The cost of stress resistance: construction and maintenance costs of leaves and roots in two populations of Quercus ilex - Laureano, Raquel G; Lazo, Yalín O; Linares, Juan C; Luque, Alfredo; Martínez, Feliciano; Seco, José I; Merino, José (Tree Physiology, 2008)
We tested whether growth and maintenance costs of plant organs vary with environmental stress. Quercus ilex L. seedlings from acorns collected from natural populations in the northern Iberian Peninsula and in a lower elevation and putatively less stressful habitat in the southern Iberian Peninsula were grown in pots under the same conditions. Growth and maintenance respiration were measured by CO2 exchange. Young leaves from 5-month-old seedlings of both populations had similar mean specific leaf areas, nitrogen and carbon concentrations and specific growth rates, and almost identical growth costs (1.26 g glucose g−1). Leaf maintenance cost was higher in northern than in the southern population (27.3 versus 22.4 mg glucose g−1 day−1, P < 0.01). In both populations, leaf maintenance cost decreased by 90% as leaves aged, but even in mature leaves, the maintenance cost was higher in the northern population than in the southern population (3.38 versus 2.53 mg glucose g−1 day−1, P < 0.01). The growth costs of fine roots < 1 mm in diameter were similar in the two populations (1.20 g glucose g−1), whereas fine root maintenance cost was higher in the northern population than in the southern population (9.86 versus 7.45 mg glucose g−1 day−1; P < 0.05). The results suggest that the cost of organ maintenance is related to the severity of environmental stress in the native habitat. Because the observed differences in both leaves and roots were constitutive, the two populations may be considered ecotypes.
10.1093/treephys/28.11.1721
Keywords: evergreen leaves; growth respiration; maintenance respiration; mediterranean species; respiration–nitrogen re- lationships; root respiration; sclerophylly